Anthropometric Measurements of Under- five Sudanese Children in Wad Medani, Central Sudan in Comparison with Center for Disease Control and Prevention Standards - Ahmed Mohammed, Sahla Mohammed; Abdulgadir Ballal, Mansour; Babikir Saad, Hydar Elhadi; Abdoun, Ghada Tajelsir (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 2 (2014), 2014)
A normal growth pattern is a gold standard by which clinicians assess the health and well being of children. The main goal of this study is to assess the growth pattern of healthy Sudanese children under the age of five in Medani city, Central Sudan and compare it with the CDC/NCHS Reference, also to evaluate some environmental factors that influence child growth. Cross sectional sample of 1500 Sudanese children were obtained from five areas, which statistically selected to represent the city. Questionnaire was designed to include, personal data, parental factors, socioeconomic status, nutrition and anthropometric measurements. The study revealed that, the mean weight and length of infants included in the data depicted a similar pattern to that of CDC/NCHS reference during the first six months. After six month, the distribution of length, height, weight and BMI for age were shifted below median of the CDC reference. Weight for length of the data depicted a similar pattern to that of the CDC curves while there is a notable deviation of weight for height of data below the CDC reference, on the other hand, there was a positive association of age with weight, length, height and BMI indicating that,  it's a normal data . Based on CDC cut offs, the prevalence of underweight and overweight were 20.7% and 18.9% respectively. Many factors have been found to influence length and weight, these factors include gender, race, hypertension during pregnancy, father education and occupation, family income, number of meals per day and all food types, while mother's age at delivery, nutrition during pregnancy, mother's education and occupation and family size were significantly related to child weight. Diabetes mellitus in pregnancy affected child length. Meat and bread intake was found to be significant variables in child height. Mother's occupation, number of meals per day and food groups had significant effect on child BMI. Important differences in weight, length, height and BMI were found between children above six months included in this study and CDC/NCHS reference, therefore interpreting their growth by comparing them to CDC/NCHS reference may not be appropriate. The reference values obtained in this study is recommended to be used in the medical practice as well as the field of medical education in Sudan.